A Literary and Comparative Study of the Ramayana - Dr. Nirmohi Phadke (Samā Jiva Jnānam (International Journal of Social Studies), 2025)
The Ramayana, one of the most revered epics of ancient India, continues to hold immense literary, cultural, and philosophical significance across centuries. This research undertakes a literary and comparative study of the Ramayana by analyzing its narrative structure, character development, thematic depth, and stylistic elements across different versions and regional adaptations. The study explores the Valmiki Ramayana as the classical Sanskrit source text and compares it with its various reinterpretations such as Tulsidas’s Ramcharitmanas, Kamban’s Ramavataram, and other folk and modern retellings from South and Southeast Asia. This comparative analysis highlights the variations in cultural values, narrative focus, and moral interpretations, while also emphasizing the common thematic core centered on dharma (duty), devotion, sacrifice, and the conflict between good and evil. Through this literary lens, the study examines how different societies and traditions have reimagined the Ramayana to reflect their unique historical, ethical, and religious perspectives.